"Doing Trust": How Researchers Conceptualize and Enact Trust in Their Research Practice. (October 2016) - Guillemin, Marilys; Gillam, Lynn; Barnard, Emma; Stewart, Paul; Walker, Hannah; Rosenthal, Doreen
Trust in research is important but not well understood. We examine the ways that researchers understand and practice trust in research. Using a qualitative research design, we interviewed 19 researchers, including eight researchers involved in Australian Indigenous research. The project design focused on sensitive research including research involving vulnerable participants and sensitive research topics. Thematic analysis was used to analyze the data. We found that researchers' understanding of trust integrates both the conceptual and concrete; researchers understand trust in terms of how it relates to other similar concepts and how they practice trust in research. This provides a sound basis to better understand trust in research, as well as identifying mechanisms to regain trust when it is lost in research.